Kenoplumbomicrolite, (Pb, □)2Ta2O6[□, (OH), O], a new mineral from Ploskaya, Kola Peninsula, Russia. (28th October 2018) - Atencio, Daniel; Andrade, Marcelo B.; Bindi, Luca; Bonazzi, Paola; Zoppi, Matteo; Stanley, Chris J.; Kristiansen, Roy
ABSTRACT: This study presents a complete characterization of kenoplumbomicrolite, (Pb, □)2 Ta2 O6 [□, (OH), O], occurring in an amazonite pegmatite from Ploskaya Mountain, Western Keivy Massif, Kola Peninsula, Murmanskaja Oblast, Northern Region, Russia. Kenoplumbomicrolite occurs in yellowish brown octahedral, cuboctahedral and massive crystals, up to 20 cm, has a white streak, a greasy lustre and is translucent. The Mohs hardness is 6. Attempts to measure density (7.310–7.832 g/cm 3 ) were affected by the ubiquitous presence of uraninite inclusions. Reflectance values were measured in air and immersed in oil. Kenoplumbocrolite is optically isotropic. The empirical formula is (Pb1.30 □0.30 Ca0.29 Na0.08 U0.03 )Σ2.00 (Ta0.82 Nb0.62 Si0.23 Sn 4+ 0.15 Ti0.07 Fe 3+ 0.10 Al0.01 )Σ2.00 O6 [□0.52 (OH)0.25 O0.23 ]Σ1.00 (from the crystal used for the structural study) and (Pb1.33 □0.66 Mn0.01 )Σ2.00 (Ta0.87 Nb0.72 Sn 4+ 0.18 Fe 3+ 0.11 W0.08 Ti0.04 )Σ2.00 O6 [□0.80 (OH)0.10 O0.10 ]Σ1.00 (average including additional fragments). The mineral is cubic, space group Fd 3 m . The unit-cell parameters refined from powder X-ray diffraction data are a = 10.575(2) Å and V = 1182.6(8) Å 3, which are in accord with those obtained previously from a single crystal of a = 10.571(1) Å, V = 1181.3(2) Å 3 and Z = 8. The mineral description and its name have been approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association (IMA2015-007a).